2009
DOI: 10.1152/ajpheart.01164.2008
|View full text |Cite
|
Sign up to set email alerts
|

Calcium/calmodulin-dependent protein kinase II mediates cardioprotection of intermittent hypoxia against ischemic-reperfusion-induced cardiac dysfunction

Abstract: Intermittent high-altitude (IHA) hypoxia-induced cardioprotection against ischemia-reperfusion (I/R) injury is associated with the preservation of sarcoplasmic reticulum (SR) function. Although Ca(2+)/calmodulin (CaM)-dependent protein kinase II (CaMKII) and phosphatase are known to modulate the function of cardiac SR under physiological conditions, the status of SR CaMKII and phosphatase during I/R in the hearts from IHA hypoxic rats is unknown. In the present study, we determined SR and cytosolic CaMKII acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 46 publications
2
27
0
Order By: Relevance
“…Taken together, these observations support the view that Bcl-2 acts as the downstream target of ROS/JAK2/STAT3 pathways and contributes to the IHH-maintained Ca 2+ homeostasis through binding to the SERCA2 and preserving the SERCA2 activity during reperfusion. The cardioprotection of IHH on the postischemic SERCA2 expression and activity is consistent with the previous reports [12,16,19]. IHH attenuates the I/R-induced Ca 2+ overload and cell contraction dysfunction via the improvement of SERCA2 expression and activity, and the latter effect is at least in part mediated by the ROS production at the early reperfusion and the subsequent activation of STAT3.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Taken together, these observations support the view that Bcl-2 acts as the downstream target of ROS/JAK2/STAT3 pathways and contributes to the IHH-maintained Ca 2+ homeostasis through binding to the SERCA2 and preserving the SERCA2 activity during reperfusion. The cardioprotection of IHH on the postischemic SERCA2 expression and activity is consistent with the previous reports [12,16,19]. IHH attenuates the I/R-induced Ca 2+ overload and cell contraction dysfunction via the improvement of SERCA2 expression and activity, and the latter effect is at least in part mediated by the ROS production at the early reperfusion and the subsequent activation of STAT3.…”
Section: Discussionsupporting
confidence: 91%
“…IHH attenuates the I/R-induced Ca 2+ overload and cell contraction dysfunction via the improvement of SERCA2 expression and activity, and the latter effect is at least in part mediated by the ROS production at the early reperfusion and the subsequent activation of STAT3. Of note, IHH may preserve postischemic SERCA2 activity through at least two additional mechanisms: (i) the maintenance of the protein level of SERCA2 during reperfusion, though the mechanisms need to be elucidated; (ii) the removal of PLB inhibition to SERCA2 by upregulating dual-site PLB phosphorylation at Ser 16 and Thr 17 via the activation of cAMPdependent protein kinase (PKA) and Ca 2+ -calmodulin-dependent protein kinase II [16,19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ser16 sites seems to be the most vital phosphorylation site with many studies highlighting its necessity to induce any effect on Serca activation (65). However, thr17 has become a target of interest specifically in studies looking at compensatory effects during ischemia reperfusion injury and coronary artery occlusion (66). It has been shown that CaMKII phosphorylation of PLB may play a role in frequencydependent acceleration of relaxation which is altered in failure (67), although recent evidence argues against a prominent role in this regulation (68).…”
Section: Calcium Transient Declinementioning
confidence: 99%